Effect of Supplementing Dairy Goat Diets With Rapeseed Oil or Sunflower Oil on Performance, Milk Composition, Milk Fatty Acid Profile, and in vitro Fermentation Kinetics - Vargas-Bello-Pérez, Einar; Pedersen, Nanna Camilla; Khushvakov, Jaloliddin; Ye, Yongxin; Dhakal, Rajan; Hansen, Hanne H.; Ahrné, Lilia; Khakimov, Bekzod (Frontiers in Veterinary Science, 2022)
The aim of this study was to determine the effect of supplementing dairy goat diets with rapeseed oil and sunflower oil on performance, milk composition, milk fatty acid profile, and in vitro fermentation kinetics. Nine Danish Landrace goats with 42 ± 5 days in milk were allocated to three treatment groups for 42 days. Animals received a basal diet, formulated with a 85:15 forage:concentrate ratio, and the basal diet was supplemented with either rapeseed oil or sunflower oil at 4% of dry matter. Goat milk was sampled on days 14, 21 and 42. Milk composition was similar between treatments. From day 14 to day 42, milk yield was increased (1.03 vs. 1.34 kg/d), while milk fat (2.72 vs. 1.82 g/d) and total solids (11.2 vs. 9.14 %) were reduced. Compared to control and rapeseed oil, sunflower decreased (P < 0.05) C4:0 (1.56 and 1.67 vs. 1.36 g/100g) and both oils decreased (P < 0.05) C18:3n3 (0.60 vs. 0.20 and 0.10 g/100g). Rapeseed oil increased (P < 0.05) C18:2 cis9, trans11 compared to control and sunflower oil (0.37 vs. 0.13 and 0.19 g/100g). Untargeted milk foodomics revealed slightly elevated (P < 0.05) gluconic acid and decreased hippuric acid (P < 0.05) in milk of oil fed goats compared to control. In vitro dry matter degradation (63.2 ± 0.02 %) was not affected by dietary treatments, while individual volatile fatty acid proportions, total volatile fatty acids (35.7 ± 2.44 mmol/l), CO2 (18.6 ± 1.15 mol), and CH4 (11.6 ± 1.16 mol) were not affected by dietary treatments. Sunflower oil and rapeseed oil decreased (P < 0.05) total gas production at 24 and 48 h compared with control. Overall, the use of sunflower oil or rapeseed oil at 4% DM inclusion did not compromised animal´s performance and milk composition.